SISTEM INFORMASI MANAJEMEN KEUANGAN BERBASIS WEB MENGGUNAKAN METODE WATERFALL PADA KOPERASI KONSUMEN TENGGUN MANIS LESTARI GANDRUNGMANGU - Harina Budi Mulyani, (2023)
The rapid development of information technology has significantly influenced various aspects of human life, such as politics, economy, social dynamics, culture, religion, education, and more. Information and communication technology has become a reliable supporting tool in carrying out the operations of companies and organizations. The same applies to cooperatives; if they aspire to be competitive, they must leverage information and communication technology as a supportive tool for their reliable operations. Tenggun Manis Lestari Cooperative is a consumer cooperative under the Ministry of Cooperatives and Small and Medium Enterprises (UKM) and the Ministry of Trade in Cilacap Regency, with a membership of 143 individuals. Tenggun Manis Lestari Consumer Cooperative is involved in the distribution of Refined Crystal Sugar (GKR) with a monthly turnover of 18.6 billion. According to interviews conducted with representatives of Tenggun Manis Lestari Cooperative, it was revealed that the cooperative has not yet utilized and optimized information technology in the financial reporting management process. The cooperative also expressed the need for a system that can facilitate efficient financial reporting management. Therefore, the author is interested in developing a web-based financial management information system for Tenggun Manis Lestari Cooperative using the waterfall method. The objective is to create a web-based cooperative financial management information system capable of processing financial reports, facilitating the financial transaction processing, and enabling stakeholders to monitor and evaluate the financial reports of Tenggun Manis Lestari Cooperative.